Notes on the Presence of Combtooth Blennies (Blenniiformes: Blenniidae) in Lampung Province, Sumatra, Indonesia - Gusti Ayu Widayanti; Delon Dian Putra; Ina Aprillia; Aulia Salsabila; Nur Arifah; Muhammad Aflah; Ayu Karlina; Muhammad Iqbal (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2026)
Combtooth Blennies (Blenniiformes: Blenniidae) are small, cryptic coastal fishes that are often underrepresented in regional ichthyofaunal surveys. Lampung Province, located at the southern tip of Sumatra, encompasses diverse coastal habitats suitable for blenniid fishes; however, information on their occurrence remains limited. Here, we present preliminary records of Combtooth Blennies from Lampung Province, based on field observations and photographic documentation conducted between 2017 to 2025, complemented by verified citizen-science records. A total of seven taxa representing five genera were recorded, including Alticus saliens. Aspidontus taeniatus, Entomacrodus vermiculatus, Istiblennius sp., Istiblennius dussumieri, Salarias sp. and Salarias fasciatus. Records were obtained from multiple coastal districts and habitats, including rocky intertidal zones, shallow reefs and nearshore coastal areas. Istiblennius dussumieri was the most frequently recorded species and was widely distributed across the study area. The findings provide essential baseline data on the distribution of Blenniidae in Lampung Province, emphasizing the importance of targeted surveys alongside citizen-science initiatives for documenting cryptic coastal fish diversity in southern Sumatra.